Dynamic R2' Imaging can Be a Biomarker for Diagnosing and Staging Early Acute Kidney Injury in Animals - Zhang, Bihui; Yao, Ziping; Gao, Weizheng; Wang, Chengyan; Kong, Hanjing; Zhang, Jue; Yang, Min (Frontiers in Medicine, 2021)
Background: Early diagnosis of acute kidney injury (AKI) is essential in clinical settings. None of the current biomarkers are widely applied. The combination of pulse-shifting multi-echo asymmetric spin-echo sequence (psMASE) and a modified hemodynamic response imaging (HRI) technique is promising. The purpose of this study was to evaluate the feasibility of psMASE combined with HRI in detecting early ischemic AKI in animal models of different severities. Methods: Twenty rabbits were divided into four groups (mild, moderate, and severe AKI and control groups). Transarterial embolization with different doses of microspheres was performed to establish AKI animal models of different severities. The 3T psMASE and HRI scans of kidneys were conducted. The R2*, R2 and R2' during room air and gas stimulation were acquired and the difference of R2' (dR2') was evaluated in different AKI groups. Results: The values were not different in R2* and R2 during room air and in R2* and R2 and R2' during gas stimulation. The value of R2' was significantly different during room air (P= 0.014), but the difference was only found between control and moderate/severe AKI groups (P= 0.032 and 0.022). The values of dR2' were different among groups (P<0.0001) and differences between every two groups except comparison of moderate and severe AKI groups were significant (P<0.01). Conclusion: The dR2' imaging acquired by a combination of renal psMASE and HRI technique can serve as a potential quantitative biomarker for early detection and staging of AKI.